Population genetic relationships between Casearia sylvestris (Salicaceae) varieties occurring sympatrically and allopatrically in different ecosystems in south-east Brazil - Cavallari, Marcelo Mattos [UNESP]; Gimenes, Marcos Aparecido [UNESP]; Billot, Claire; Torres, Roseli Buzanelli; Zucchi, Maria Imaculada; Cavalheiro, Alberto José [UNESP]; Bouvet, Jean-Marc (Oxford University Press, 2010)
Species delimitation can be problematic, and recently diverged taxa are sometimes viewed as the extremes of a species' continuum in response to environmental conditions. Using population genetic approaches, this study assessed the relationship between two Casearia sylvestris (Salicaceae) varieties, which occur sympatrically and allopatrically in the landscape of south-east Brazil, where intermediate types are also found.In total, 376 individuals from nine populations in four different ecosystems were sampled, and nine microsatellite markers were used to assess the relative effects of the ecosystems and varieties on the distribution of genetic diversity among populations of this species.As a by-product of this study, several PCR products with more than two alleles were observed. The possibility that extra bands represent non-specific amplification or PCR artefacts was discarded by sequencing a sample of these bands. We suggest that (partial) genome duplication in C. sylvestris most probably explains this phenomenon, which may be a key factor in the differentiation of the two taxa, as it was markedly more frequent in one of the varieties. AMOVA indicated that approx. 22 % of the total genetic diversity was found between the two varieties. Bayesian analysis identified varieties and ecosystems as evolutionary units, rather than the individual populations sampled.The results are in agreement with field observations and support the recognition of two varieties, as well as documenting the occurrence of hybridization between them.
Keywords: Atlantic Forest; Casearia sylvestris; Cerrado; ecotones; hybrid zone; microsatellites; population genetic structure; SSR; sympatry